Combining ability for capsule characters in sesame (Sesamum indicum L.): Combining ability for capsule characters in sesame (Sesamum indicum L.) - K T RAMYA; A L RATHNAKUMAR; H H KUMARASWAMY; J JAWAHARLAL; RATNAKUMAR PASALA (Journal of Oilseeds Research, 2023)
The combining ability for capsule characters was estimated in 8x8 full diallel mating design using 8 elite varieties of sesame which are cultivated across different geographical regions in India. The ratio of GCA: SCA indicated predominance of non- additive gene effects for capsule characters. Among 8 parents, GT-2 was the best general combiner of capsule width, capsule length and seed number/capsule, while TKG-22 was the best combiner for seed weight/capsule.